Potato production, marketing, and utilization in Meghalaya, India: Results of a value chain assessment. - Chulet, H.; Anantharaman, M.; Shanpru, E.; Prain, Gordon (International Potato Center, 2017)
Potato is among the most important food crop globally, its demand rising rapidly in Asia along with the steady increase in incomes and population among Asian megacities. The same is true in India, the second largest producer of potato in the world, next to China. However, despite being the top vegetable crop produced in the country; easily accessible information on its production, marketing, and utilization is still limited. This research presents the results of a value chain assessment carried out in Meghalaya, India where potato is the chief crop in terms of volume and value. It documents the entire potato value chain in Meghalaya including input supply, varietal distribution over seasons, production, and marketing; and identifies major constraints and areas where interventions could significantly increase returns for potato producers. This study followed a value chain analysis approach and involved a cross-sectional data collection among a range of stakeholders and value chain actors through review of secondary data, key informant interviews, focus group discussions, and surveys. Results show that the potato value chain in Meghalaya begins with smallholder potato producers, and involves input suppliers, traders, aggregators, wholesalers, and retailers from within and outside the state. The average potato productivity in Meghalaya is less than half of the country average owing to the several issues farmers encounter in production. These include the lack of quality potato seeds of improved varieties, decreasing soil fertility, and other environmental stresses including climate change. There is no post-harvest processing and formal quality control being done for Meghalaya potatoes, while proper storage and transportation options are limited, which affects potato prices. This study recommends specific actions to improving potato marketing including providing market intelligence to farmers to help stabilize prices, building the marketing and entrepreneurial capacity of farmers, identifying processing options, and developing a branding strategy for Meghalaya potatoes to market to other states. All these can be done through better collaboration between farmers, other value chain actors, and government agencies. These results can be used by policy makers, research workers, and development organizations interested in value chain development of potato to help improve the livelihood of smallholder potato farmers and other actors in the potato value chain.